The road to successful implementation of innovation in radiotherapy: A research-based implementation protocol - Ho, Fiona; Swart, Rachelle; Boersma, Liesbeth; Fijten, Rianne; Cremers, Paul; van Merode, Frits; Jacobs, Maria; Alongi, Filippo; Belderbos, José; Bhattacharya, Indrani S.; Buijsen, Jeroen; van Dieren, Erik; et al. (Radiotherapy and oncology, 2025)
•First scientific implementation protocol for innovations in radiotherapy.•The protocol was developed using literature review, interviews, and a Delphi study.•High consensus on the protocol in Delphi study among RT and implementation experts.•Differing perceptions were found between RT and implementation experts.•The protocol aims to improve RT innovation adoption and patient care. Radiotherapy (RT) is rapidly advancing, yet only 50 % of innovations are implemented promptly. Despite the availability of Implementation Science (ImpSci) theories, models, and frameworks (TMFs), a theory–practice gap persists in effectively applying these insights in RT clinical practice. This study aims to develop a consensus-based implementation protocol for RT innovations using validated ImpSci knowledge. A literature review of TMFs (May–August 2023) and 20 semi-structured interviews with Dutch RT professionals (August–December 2023) identified key RT components for implementation. These insights informed a draft RT implementation protocol, which was refined through a three-round international Delphi study (March–September 2024) involving 11 RT and 5 ImpSci experts. Consensus was determined using a 5-point Likert scale, analysing medians, interquartile ranges (IQRs), and percentage scoring. The Knowledge-to-Action (KTA) Framework and input from expert interviews were used to draft the protocol. Delphi response rates were 100 %, 93.8 %, and 88.9 % across rounds. In round 1, 88.9 % of elements achieved consensus (median = 4.0, IQR = 0.0–1.3); only the application of a prediction model for timely implementation (step 3c) needed revision after rounds 1 and 2. In round 3, also for step 3c consensus was reached (median = 4.0, IQR = 0.3). The protocol includes defining innovation types, stakeholder analysis, tailored implementation strategies, and a phased evaluation plan to ensure sustainability. This is the first consensus-based RT innovation implementation protocol, addressing the theory–practice gap with a structured clinical approach. Future research should validate the protocol and assess the impact of preparation on implementation success.